Muhammadiyah's Initiatives in Preparing Muballigh: Empirical Study on Muhammadiyah Higher Education Institutions - Choirin, Muhammad; Kamal, Fathurahman; Masuwd, Mowafg; Suparto; Abdulghani, Naser Ali (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
The concepts of Islamic education and da’wah have garnered significant scholarly interest; however, most prior research remains theoretical, lacking a detailed examination of how Islamic universities operationalize curricula to cultivate future da’wah leaders. This study fills that gap by investigating how Muhammadiyah Higher Education (MHE), Perguruan Tinggi Muhammadiyah (PTM), systematically prepares the next generation of da’is or preachers. Employing a qualitative-descriptive methodology, data were collected through document analysis, curriculum review, and semi-structured interviews with academic leaders. The analysis demonstrates that MHE has integrated Muhammadiyah values across its curricula and established a formal collaboration with the Asia Muslim Charity Foundation (AMCF) to strengthen students’ Arabic proficiency and Islamic literacy, competencies essential for da’wah roles. These innovative strategies show how MHE not only provides ideological formation but also technical preparation for da’wah practitioners. This article thus presents a concrete model of how an Islamic educational institution integrates da’wah within its academic structures, making both theoretical and practical contributions to the broader discourse on Islamic higher education.